89 - NUTRITIONAL STATUS OF CHILDREN OF THE NETWORK OF MUNICIPAL PUBLIC ELEMENTARY SCHOOL CITY OF MACAPÁ-AP (Fiep Bulletin - online, 2011)
The study aimed to investigate the nutritional status of children 07 to 10 years of primary education in public and urban area of Macapá (AP). The sample consisted of 2071 elementary school students of both sexes, enrolled, selected by proportional random sampling by schools and conglomerate class. As a tool for checking the weight of school children used a digital scale with a capacity of 150 kg and a stadiometer tape type, with 2000 cm with an accuracy of 01 mm. Anthropometric evaluation was done by weight, height and age. Nutritional status was assessed by the criterion of WATERLOW (1976), the benchmark was the NCHS. Inferential comparison between groups was performed using the chi-square (x2). With the level of significance of the null hypothesis of 5% (p
Keywords: Nutritional status; obesity; malnutrition